Neonatal brain MRI to prognosticate neurodevelopmental outcomes in fetal growth restricted infants: a systematic review - Ramdial, Randy; MacNamara, Madeline A.; Moldrich, Randal; Colditz, Paul B.; Wixey, Julie A. (Frontiers in Pediatrics, 2026)
AimThe purpose of this study was to identify magnetic resonance imaging (MRI) brain markers at birth that prognosticate neurodevelopmental outcomes at ≥12 months of age in fetal growth restricted (FGR) infants.MethodsA systematic literature search was undertaken in PubMed, Embase, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Scopus in March 2025. Articles were assessed by two reviewers. The inclusion criteria included papers relating to infants with birth weight <10th percentile, with assessed neurodevelopmental outcomes at 12 months of age or older, and MRI performed at birth with markers for neurodevelopment, and comparison of data to appropriate for gestational age (AGA) infants. The quality of studies was assessed using the Cochrane-approved Quality in Prognosis Studies tool.ResultsThree articles met the inclusion criteria. All demonstrated a correlation between MRI in regions of the brain and neurodevelopmental outcomes >12 months of age across all studied infants. However, only one of the three studies correlated early MRI results with neurodevelopmental outcomes specifically in FGR infants and thus a meta-analysis could not be performed. The single study reports a positive correlation between MRI total parenchyma area and cognitive scores in FGR infants.ConclusionThe current literature highlights the developmental risk in FGR vs. AGA infants. FGR neonates have significantly different MRI results compared to AGA neonates and MRI findings in the neonate are associated with adverse neurodevelopmental outcomes. However, current evidence is insufficient to firmly establish MRI prognostic capabilities specifically for FGR infants. Sub-group analysis of the FGR cohort in the reported studies and the use of more advanced MRI techniques would likely elucidate this. Further research is required to ascertain robust clinical MRI markers of early adverse brain development in the FGR newborn.Systematic Review Registrationidentifier CRD42023400436